2020
DOI: 10.3390/medicina56090476
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Successive Exposure to Bleaching and Fluoride Preparations on the Surface Hardness and Roughness of the Aged Resin Composite Restoratives

Abstract: Background and Objectives: Surfaces of composite restorations are adversely affected upon bleaching and topical fluoride application. Such a procedure is normally carried out in the presence of restorations already serving in a different oral environment, although previous in vitro studies only considered the freshly-prepared composite specimens for assessment. The current study accordingly aimed to evaluate both the surface hardness and roughness of aged composite restoratives following their successive expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
1
8
0
2
Order By: Relevance
“…The results of the current study suggest that the roughness increased at the surfaces of all samples subjected to the bleaching protocols, in complete accordance with specialty literature [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current study suggest that the roughness increased at the surfaces of all samples subjected to the bleaching protocols, in complete accordance with specialty literature [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is called into question whether these types of gels, indicated by the dentist, have a mild or strong effect only on natural teeth or dental restorations. Because the bleaching agent acts on the surface of the teeth or restorations, it was observed that it may affect fracture toughness of resin-based composite restorations [ 30 , 31 ]] and may lead to release of some organic matrix polymers in the oral environment [ 32 ]. According to Schuster L. et al, bleaching procedures may cause reduced or enhanced elution of chemicals from the composites [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent resin composites typically express surface and optical properties that closely mimic those of the natural dental structure and demonstrate attractive clinical endurance [17]. Resin-based composites are comprised of a matrix of organic substances, coupling agents and inorganic fillers, and other elements such as polymerization inhibitors, initiators, accelerators, photosensitizers, and photoinitiators.…”
Section: Introductionmentioning
confidence: 99%